STUDY OF CARBON TRACE AND STORAGE IN GROUNDWATER USING HYDROGEOCHEMICAL AND STABLE ISOTOPE ANALYSIS - Abdillah, Faizal
Study of carbon trace and storage in groundwater in the Jakarta Groundwater Basin aims to determine changes in isotopic composition in the carbon cycle and carbon storage in groundwater due to increases in CO2 concentrations in the air. The method for tracing the carbon cycle in groundwater uses chemical analysis and natural isotopes ? 13C, ? 18O and ? 2H as well as calculating the partial pressure of CO2 in water samples (groundwater, rainwater, surface water and seawater) and gas samples (atmospheric gas and vehicle emissions). The analysis results show that the dominant groundwater facies in the unconfined aquifer system is Ca-HCO3 and the confined aquifer system is Na-HCO3. Groundwater dilution by rainwater is recorded from a decrease in TDS values and changes in the ? 18O isotope composition. Changes in unconfined aquifers from an average of 326 mg/L to 320 mg/L and confined aquifers from an average value of 806 mg/L to 752 mg/L as well as changes in the isotopic composition of ? 18O which is depleted in unconfined aquifer groundwater (-5,7 ‰ to -6,5 ‰) and confined aquifers (-5,9‰ to -6,3‰). For the ? 2H value, enrichment occurs with a value of -37,5 ‰ to -34,0 ‰ in the unconfined aquifer and -37.3 ‰ to -36.2 ‰ in the confined aquifer. This change indicates the presence of carbon gas mixed in the groundwater. Traces of the carbon cycle can be traced through changes in the ?¹³C isotope composition which in the Jakarta Groundwater Basin reflects the influence of anthropogenic factors, namely the burning of fossil fuels with a ?¹³C value of around -23 ‰. As a result, the value of ?¹³C in the atmosphere has decreased from -9 ‰ to -13 ‰. The gas diffuses into rainwater and change pCO2 of around 1,47-2,46% with ? 13C in the range - 14 ‰ to -19 ‰. Rainwater infiltration into unconfined aquifer groundwater has more dynamic changes with ? 13C in the range -9 ‰ to -13 ‰ and pCO2 1,30-1,39 % compared to confined aquifer systems which are more stable ? 13C in the range -8 ‰ to -10 ‰ and pCO2 0,45 – 0,57 %. Based on the results of groundwater pCO2 calculations, unconfined aquifers store approximately ± 3 times more CO2 than confined aquifers